The benzalkonium chloride resistant or sensitive phenotype of Listeria monocytogenes planktonic cells did not dictate the susceptibility of its biofilm counterparts. (September 2019) - Barroso, I.; Maia, V.; Cabrita, P.; Martínez-Suárez, J.V.; Brito, L.
Abstract: The main goal of this work was to approach food industry conditions in the comparison of the susceptibility of biofilms of Listeria monocytogenes to the biocides benzalkonium chloride (BAC) and peracetic acid (PAA). Twelve isolates of L. monocytogenes, including nine well characterized BAC resistant strains were used. Biofilms were produced on stainless steel coupons (SSC), at 11 °C (refrigeration temperature) or at 25 °C (room temperature), in culture media simulating clean (nutrient limiting) or soiled (nutrient rich) growth conditions. Neither different nutrient availability nor growth temperature showed significant effect ( p  > .05) on biofilm formation. PAA confirmed to be more effective than BAC in biofilm elimination. Biofilms formed under nutritional stress tended to differentiate more the response to BAC of the resistant or sensitive strains, but the resistant or sensitive phenotype of the planktonic cells did not dictate biofilm susceptibility. Graphical abstract: Unlabelled Image Highlights: Resistant or sensitive strain phenotype did not dictate biofilm susceptibility. Biofilm formation was not affected by nutrient availability nor growth temperature. Biofilms grown under nutrient scarcity differentiate more their response to BAC.